Plyo-accentuated eccentric loading methods to enhance lower limb muscle power - Handford, M. J.; Rivera, F. M.; Maroto-Izquierdo, S.; Hughes, J. D. (Strength and Conditioning Journal, 2021)
Accentuated eccentric loading (AEL) can be combined with lower-body power-based movements to acutely enhance them; however, currently, there are limited recommendations for this training method. AEL can enhance force and power metrics during its utilization with lower-body power-based exercises. When using AEL, exercises should consist of jump squats and countermovement jumps with loading methods consisting of weight releasors or dumbbell hand release. Elastic bands can be used; however, more research is needed in this area. External loads ranging from 10-30% of body mass can be used. Future research needs to investigate increased eccentric and concentric loads when using AEL with power-based movements.